2012
DOI: 10.1139/z2012-093
|View full text |Cite
|
Sign up to set email alerts
|

Variation in catchment areas of Indiana bat (Myotis sodalis) hibernacula inferred from stable hydrogen (δ2H) isotope analysis

Abstract: Understanding seasonal movements of bats is important for effective conservation efforts. Although female Indiana bats ( Myotis sodalis Miller and Allen, 1928) have been documented to migrate >500 km, knowledge of their migratory patterns is still extremely limited. We used the relationship between latitude and stable hydrogen isotope ratio in bat hair (δ2Hhair) to estimate the north–south extent of the summer range (catchment area) of bats hibernating in 14 Indiana bat hibernacula in eight states throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Quay (1970) provided a brief review of moulting in bats and suggested that, in general, bat species grow new fur once annually (usually in late summer-fall) and that males tend to grow new fur before females. Because fur is increasingly being used in endogenous marker analyses for studies of bat ecology (e.g., Cryan et al 2004Cryan et al , 2012Voigt and Kelm 2006;Britzke et al 2009Britzke et al , 2012Painter et al 2009;York and Billings 2009;Fraser et al 2010Fraser et al , 2012Erzberger et al 2011;Ossa et al 2012;Popa-Lisseanu et al 2012;Sullivan et al 2012;Voigt et al 2012aVoigt et al , 2012bVoigt et al , 2013, there is renewed interest in understanding the moulting cycle on a species by species basis. Since the review by Quay (1970), numerous papers reporting moulting data in various bat species have been published (e.g., Davis and Barbour 1970;Kunz 1973Kunz , 1974Young 1975;Timm 1989;Ilyin 1990;Voigt et al 2003;Cryan et al 2004Cryan et al , 2012Tiunov and Makarikova 2007;Alagaili et al 2011;Fraser et al 2012).…”
Section: Moulting In Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quay (1970) provided a brief review of moulting in bats and suggested that, in general, bat species grow new fur once annually (usually in late summer-fall) and that males tend to grow new fur before females. Because fur is increasingly being used in endogenous marker analyses for studies of bat ecology (e.g., Cryan et al 2004Cryan et al , 2012Voigt and Kelm 2006;Britzke et al 2009Britzke et al , 2012Painter et al 2009;York and Billings 2009;Fraser et al 2010Fraser et al , 2012Erzberger et al 2011;Ossa et al 2012;Popa-Lisseanu et al 2012;Sullivan et al 2012;Voigt et al 2012aVoigt et al , 2012bVoigt et al , 2013, there is renewed interest in understanding the moulting cycle on a species by species basis. Since the review by Quay (1970), numerous papers reporting moulting data in various bat species have been published (e.g., Davis and Barbour 1970;Kunz 1973Kunz , 1974Young 1975;Timm 1989;Ilyin 1990;Voigt et al 2003;Cryan et al 2004Cryan et al , 2012Tiunov and Makarikova 2007;Alagaili et al 2011;Fraser et al 2012).…”
Section: Moulting In Mammalsmentioning
confidence: 99%
“…The use of endogenous markers to study migration has many benefits, including the requirement for only a small tissue sample that is usually collected nonlethally and the need to capture the study animal only once. Given the challenges inherent in capturing and tracking many species of bats, these techniques are promising for future bat research, and there are already many examples of studies using stable isotope analyses to study bat migration (Fleming et al 1993;Cryan et al 2004;Fraser et al 2010;Erzberger et al 2011;Britzke et al 2012;Fraser et al 2012;Ossa et al 2012;Popa-Lisseanu et al 2012;Sullivan et al 2012;Voigt et al 2012a). Fewer studies have examined trace element or strontium isotope compositions in bat tissues (but see Hickey et al 2001;Allinson et al 2006;Gashchak et al 2010;Ghanem et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some research on bird migratory systems have successfully used stable hydrogen isotope techniques to detect smaller scale movements of organisms across elevations, e.g., [ 58 , 59 ], but attempts to do this with bats have so far had limited success [ 40 , 60 , 61 ]. Researchers have used stable hydrogen isotope techniques to estimate the origins of individual bats captured or collected at important features such as wind energy facilities, e.g., [ 31 , 34 ], or hibernacula, e.g., [ 62 , 63 ]. Others seek to identify continental scale patterns in migratory movements by sampling bats across locations, often using museum specimens, e.g., [ 28 , 29 , 30 ].…”
Section: Intrinsic Markers In Studies Of Bat Migrationmentioning
confidence: 99%
“…Research in both the U.S. and Germany has shown that bat fatalities at wind energy facilities include both local and migratory bats in varying proportions [ 19 , 31 , 32 ]. Research at hibernacula and swarming sites has identified sites with greater and lesser catchment areas [ 62 , 64 ] and has revealed changes over time in bat migratory habits [ 63 ]. There is clear evidence that many bat species have partial and differential migratory patterns, with variation among sexes [ 19 , 20 , 29 , 63 ], age groups, e.g., [ 65 , 66 ], and among bats with varying anatomy [ 63 ].…”
Section: Intrinsic Markers In Studies Of Bat Migrationmentioning
confidence: 99%